Genetic counselling in multiple sclerosis: risks to sibs and children of affected individuals. - Sadovnick, A; Dircks, A; Ebers, G (1999)
Genetic factors are recognized as having important roles in both the overall etiology and the familial aggregation of multiple sclerosis (MS), leading to increased requests for genetic counselling. This paper is designed to provide familial risk data in a practical format for use during genetic counselling for MS. Depending on the amount of genetic sharing among family members, the relative risk of MS compared with that for the general population can range from 1 (adopted sibs and children of the MS proband, with whom they share no genetic material) to 190 (monozygotic co-twins of MS patients, with whom they share 100% of their genetic material). When counselling full sibs of MS patients, risks can be better calculated if information is available on the age of MS onset in the patient and whether or not one parent has MS.